Item Analysis - Sasmita Sasmita; Pungky Dyantieni; Yulia Dini Astuti; Yayan Sudrajat (PT. Lancar Media Komunikasi, 2022)
The purpose of writing this article is to describe the items, explain the purpose of making item analysis,find out the level of difficulty of the items, know the techniques for compiling item analysis, and knowthe advantages and disadvantages of qualitative and quantitative techniques. The task of a teacher besides teaching and guiding, is to assess the learning outcomes of their students. Assessing activities in the learning process is also known as learning evaluation. Evaluation is needed to see the level of success in the implementation of learning which will be used as the basis for making the final decision. Keywords: Item analysis, item difficulty level, technique of compiling item analysis, advantages anddisadvantages of qualitative and quantitative techniques.